The Influence of Remote Working and Organizational Support on Work Engagement with Job Satisfaction as a Mediating Variable in Service Sector Companies in Indonesia - Nurul Iman; Elly Yuniar Nitawati (Journal of Economic Education and Entrepreneurship Studies, 2025)
This study aims to analyze the influence of remote working and perceived organizational support (POS) on work engagement, with job satisfaction as a mediating variable, among employees in the service sector in Indonesia. The research adopts a quantitative descriptive-correlational approach, involving 100 respondents selected through purposive sampling. Data were collected using an online Likert-scale questionnaire and analyzed using descriptive statistics, validity and reliability tests, Pearson correlation, and path analysis to examine both direct and indirect relationships among variables.The results indicate that both remote working and POS have a direct, positive, and significant influence on job satisfaction. Furthermore, job satisfaction directly affects work engagement. A significant mediation effect was also found, showing that job satisfaction serves as a key link in explaining how remote working and POS can enhance employee engagement. These findings highlight the importance of work experience quality in the context of flexibility and organizational support.Theoretically, this study contributes to the literature on modern work relationships and reinforces the role of job satisfaction as a key psychological variable in promoting work engagement. Practically, the findings can serve as a foundation for service sector management to develop flexible work policies and supportive organizational systems that are not only efficient but also prioritize employee well-being.